Genetic diversity of tomato germplasm resources resistant to bacterial wilt (Ralstonia solanacearum) revealed by AFLP - ZHOU Guo-zhi; LI Zhi-miao; YANG Yue-jian; XING Juan; WANG Rong-qing (浙江大学学报. 农业与生命科学版)
The relationship and genetic diversity of 20 tomato germplasm resources resistant or susceptible to bacterial wilt (Ralstonia solanacearum) were analyzed by AFLP (amplified fragments length polymorphism)-silver staining approach. Five primer combinations selected from 64 primer pairs revealed a total number of 201 unambiguous bands, 74 of which were polymorphic with a polymorphism frequency of 36.8%. This result showed moderate variations of some enzyme digestion sites among the used tomato germplasm resources. As analyzed by NTSYS software, the genetic similarity coefficient of 20 tomato resources ranged from 0.76 to 1.00. Based on the coefficient value of 0.88, these tomato germplasm resources were clustered into 2 multiple-member groups and 5 one-member groups by UPGMA (unweighted pair group method with arithmetic mean) analysis, which provided molecular reference for parent selection in breeding tomato for resistance to bacterial wilt.